Length-weight relationship and condition factor of Tade gray mullet, Chelon planiceps (Valenciennes, 1836) from Hooghly-Matlah Estuary, West Bengal, India - Soumendra Pramanick; Sudhir Kumar Das; Dibakar Bhakta; Canciyal Johnson (Journal of Fisheries, 2017)
Tade gray mullet (Chelon planiceps) forms a lucrative fishery in the Hooghly-Matlah estuarine system. During eight months of investigation 232 specimens were examined to study length-weight relationship and relative condition factor (Kn). The length and weight of fish was varied from 41 to 283 mm and 0.81 to 208 g respectively. Two length-weight relationship equations were obtained from the analysis, W=0.0000397L2.952 for <187 mm size group and W=0.0000406L2.834 for >187 mm size group. The size at first maturity was recorded as 187 mm. The b value was not significantly different from 3 indicating isometric growth. The monthly mean Kn for the male and female were 1.041–1.125 and 1.009–1.236 respectively. The highest Kn value was recorded in July for both the sexes, which may be due to advance maturity stages. The present study will be useful in the context of biological management of mullet fishery as well as to find out aqua-farming potential of Tade gray mullet.